(untitled) (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 1993)
The thought presented emerged from personal experience and reflection, and informal interviews. Eleven reasons proposed by those people interested in physics, includes its level of difficulty; its structure and formal operation; gap between physics and physics education; grade on physics as the indicator of students’quality; nonselective equpments used in lower secondary level; mismatch between students’ conseptlons and and their scientific concepts emerging fromvarying terms and language usage; different view of physics teachers’ love in physics and physicists’ love in history of physics; imbalance omount of concepts to be studied and effective hours in school; inappropriate topics sequence; and physics education and its presentation which favour male students. Those reasons are tentative and requiring further clarification by educationists with physics backgrounds.